Natural Resource Policy in Selected Post-Soviet Countries and Their International Trade Competitiveness - Falkowski, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Objective: The objectives of this article are: 1) to briefly present the natural resources policies of Azerbaijan, Kazakhstan and Russia, 2) to thoroughly analyse the development of long-term comparative advantages in exports of each of these countries, 3) to determine whether their competitiveness (ceteris paribus) is a consequence of the natural resources policies they pursue. Research Design & Methods: It has been assumed that the emergence or significant long-term improvement of comparative advantages in exports may prove the effectiveness of the natural resources policy. To determine the international trade competitiveness (in terms of any comparative advantages possessed) of Azerbaijan, Kazakhstan and Russia, two indexes were applied: Balassa’s Revealed Comparative Advantage (RCA) Index and the Lafay Index (LFI) of international trade specialisation. Findings: The structure of long-term comparative advantages of Azerbaijan, Kazakhstan and Russia in international trade has not changed for years, nor have any new comparative advantages appeared, which would indicate an improvement in the competitiveness of their economies. Therefore, the natural resource policies they pursue further strengthens the resource-based character of their economies, thus reducing their overall international trade competitiveness. Implications / Recommendations: Given the present situation, it seems necessary for Azerbaijan, Kazakhstan and Russia to take specific measures not only in their natural resources policies, but also in their economic policies and development strategies, which should be pragmatically oriented towards the modernisation and development of non- -resources-based sectors (ultimately increasing their competitiveness) using the funds from exports of their energy resources. Contribution: The article contributes to the research on the importance of natural resource policy for international trade competitiveness, in particular with respect to selected post-Soviet natural resources-based economies, i.e. Azerbaijan, Kazakhstan and Russia. It verifies the research hypothesis that, given their energy resources, the natural resource policies pursued by Azerbaijan, Kazakhstan and Russia have a negative impact on the competitive profiles of their economies. Moreover, they further strengthen their resource-based character, thus reducing their overall international trade competitiveness.